Diagnosis of Peripheral Lung Lesions via Conventional Flexible Bronchoscopy with Multiplanar CT Planning - De Roza, Marianne Anastasia; Quah, Kien Hong; Tay, Cheong Kiat; Toh, Weiquan; Li, HuiHua; Kalyanasundaram, Ganesh; Anantham, Devanand (Pulmonary Medicine, 2016)
Background. Conventional flexible bronchoscopy has limited sensitivity in the diagnosis of peripheral lung lesions and is dependent on lesion size. However, advancement of CT imaging offers multiplanar reconstruction facilitating enhanced preprocedure planning. This study aims to report efficacy and safety while considering the impact of patient selection and multiplanar CT planning. Method. Prospective case series of patients with peripheral lung lesions suspected of having lung cancer who underwent flexible bronchoscopy (forceps biopsy and lavage). Endobronchial lesions were excluded. Patients with negative results underwent CT-guided transthoracic needle aspiration, surgical biopsy, or clinical-radiological surveillance to establish the final diagnosis. Results. 226 patients were analysed. The diagnostic yield of bronchoscopy was 80.1% (181/226) with a sensitivity of 84.2% and specificity of 100%. In patients with a positive CT-Bronchus sign, the diagnostic yield was 82.4% compared to 72.8% with negative CT-Bronchus sign (p=0.116). Diagnostic yield was 84.9% in lesions > 20 mm and 63.0% in lesions ≤ 20 mm (p=0.001). Six (2.7%) patients had transient hypoxia and 2 (0.9%) had pneumothorax. There were no serious adverse events. Conclusion. Flexible bronchoscopy with appropriate patient selection and preprocedure planning is more efficacious in obtaining a diagnosis in peripheral lung lesions compared to historical data. This trial is registered with ClinicalTrials.gov Identifier: NCT01374542.